ASSOCIATION BETWEEN SENSORIAL OTOLITHIC DEFICIT AND HEARING LOSS IN CHILDREN - Constantin Guma; Cristian Marius Mârțu; Sebastian Cozma; Raluca Olariu; Luminița Rădulescu; Alexandru Stingheriu; Iustin Iațentiuc; Mădălina Georgescu; Violeta Necula; Oana Bitere-Popa (Romanian Journal of Oral Rehabilitation)
Aim of the study. This study aimed to evaluate the association between hearing loss in infants and young children and otolithic vestibular deficits, as well as the degree of correlation between the severity of hearing loss and vestibular evaluation results. Materials and methods. This research was a prospective study and enrolled 51 children (29 boys and 22 girls) with a mean age of 3,3 years. The audiological assessment protocol included tympanometry, otoacoustic emissions, auditory steady-state response, and brainstem-evoked response audiometry. The subjects were divided into two groups as follows: a normal hearing group and a group with varying degrees of hearing loss. For all patients in the study, vestibular evaluation included the saccular function assessment by cervical vestibular-evoked myogenic potential (cVEMP) and the utricular function assessment by ocular vestibular-evoked myogenic potential (oVEMP). The device used for evaluation was the Eclipse evoked potentials platform from Interacoustics®, Denmark. Results. In the normal hearing group, the presence of saccular sensor response was recorded by cVEMPs in over 91% of ears, while the utricular response recorded by oVEMPs was present in 75,68% and absent in 16,22% of ears. In the hearing-impaired group, the saccular response was recorded in 61,54% and was lacking in 30,77% of ears, the utricular response being present in 46,15% of ears with hearing loss. In 47,69% of hearing loss ears, the utricular response was absent. The otolithic function impairment was proportional to the severity of hearing loss: in the moderate hearing loss group, it was present in 36,36% of both the saccular and utricular functions, in the severe hearing loss group it was found in 36,67% of ears for the utricular function and 23,33% for the saccular function. In profound hearing loss, the saccular function deficit was present in 37,5% and a significant utricular function deficit in over 66% of ears. Conclusions. Congenital vestibular impairment is frequently associated with sensorineural hearing loss. Vestibular assessment is necessary to prevent a delay in diagnosing balance and development disorders, promoting early intervention. In our study, the impairment of otolithic function was found to be proportional to the severity grade of hearing loss. In severe and profound cases, vestibular assessment before cochlear implantation is crucial to detect potential vestibular damage and to suggest the implantation strategy by simultaneous or sequential surgery.